Validation of a potency assay for CD34 + cell based therapy - Christine Vignon; Arthur Cormier; Aurélien Goubaud; Hélène Schaffhauser; Sara Bennaoum; Eva Grotzinger; Jean-Olivier Hirsch; Philippe Hénon; Matthieu de Kalbermatten; Ibon Garitaonandia (Scientific Reports)
Abstract ProtheraCytes (expanded autologous CD34 + cells) promote regeneration by revascularising damaged myocardial tissue via angiogenesis through the secretion of vascular endothelium growth factor (VEGF). We developed a potency assay based on the quantification of the secreted VEGF during the expansion of CD34 + cells via an automated ELISA system (ELLA). This potency assay is fast, reliable, and quantitative assay that allows for the timely batch release before ProtheraCytes are shipped to the clinic for injection. Here, we describe the validation of the VEGF potency assay according to international guidelines for cell therapy products. The assay showed a linear response for the range [20 pg/mL − 2800 pg/mL] with a correlation coefficient R2 = 0.9972. Coefficients of variation for repeatability precision ≤ 10% and repeatability precision ≤ 20% demonstrated that the method is precise. The mean recoveries for each concentration observed (between 85% and 105%) showed that the method is accurate. We also demonstrated that the method is specific with a maximal VEGF concentration (2 pg/mL) in unspiked culture medium samples below the low limit of quantification (LLOQ) (20 ng/mL). The validation and the assessment of 38 clinical batches indicate that this potency assay is suitable for the release of ProtheraCytes.